2006
DOI: 10.1038/sj.bjc.6603294
|View full text |Cite
|
Sign up to set email alerts
|

The relation between socioeconomic and demographic factors and tumour stage in women diagnosed with breast cancer in Denmark, 1983–1999

Abstract: The authors investigated the association between socioeconomic position and stage of breast cancer at the time of diagnosis in a nationwide Danish study. All 28 765 women with a primary invasive breast cancer diagnosed between 1983 and 1999 were identified in a nationwide clinical database and information on socioeconomic variables was obtained from Statistics Denmark. The risk of being diagnosed with a high-risk breast cancer, that is size 420 mm, lymph-node positive, ductal histology/high histologic grade an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 38 publications
7
60
0
Order By: Relevance
“…Furthermore, mammography is now an important tool for the detection of early stages of breast cancer (Smith et al, 2003;Adibelli et al, 2009) and thus has a large influence on breast cancer stage at presentation (Dalton et al, 2006;Masi et al, 2007;Pasick et al, 2008). Previous studies have found that the implementation rate of mammography is closely related to income level: people with lower incomes have lower mammography implementation rate (Ward et al, 2008;Cunningham et al, 2009), which suggests that these patients have a higher risk of presentation with a larger, more advanced stage tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mammography is now an important tool for the detection of early stages of breast cancer (Smith et al, 2003;Adibelli et al, 2009) and thus has a large influence on breast cancer stage at presentation (Dalton et al, 2006;Masi et al, 2007;Pasick et al, 2008). Previous studies have found that the implementation rate of mammography is closely related to income level: people with lower incomes have lower mammography implementation rate (Ward et al, 2008;Cunningham et al, 2009), which suggests that these patients have a higher risk of presentation with a larger, more advanced stage tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Our occupational subgroups probably encompassed varied social conditions, and our variable socioeconomic status has no impact after adjustment. In Denmark, a population-based study of 28 765 cases (Dalton et al, 2006) showed that the risk of a high-risk breast cancer increased with reduced income, and with lower educational level. In the United States, SEER data showed that African-Americans had higher mortality even after adjustment for socio-economic factors (Grann et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Examples that are currently unavailable from cancer registry data include level of education and comorbidity. A higher level of education amongst those living in the more affluent areas may result in a higher degree of health awareness, better perception of symptoms and less delay in seeking medical care (Dalton et al, 2006), which may in turn lead to improved survival. The presence of co-morbidity has been associated with reduced survival in breast cancer (Houterman et al, 2004;Louwman et al, 2005), and patients from deprived areas may have a higher level of comorbidity (Macleod et al, 2000b).…”
Section: Socioeconomic Background Of Women With Breast Cancermentioning
confidence: 99%